Increasing Economic Capacity of Rural Community Through The Use Of Local Ecological Potency Based - Ansori, Ansori; Rosita, Tita (Universitas Negeri Semarang, 2018)
Capacity-building is a series of efforts undertaken to provide maximum capacity or output improvement. In this research, the economic capacity of rural communities is enhanced through the ecological potential in the cultural context. Therefore, this research has much to do with various forms of community life to develop all the potential environmental, potential and cultural potential of human beings there. The method used in this research is qualitative method and using triangulation approach, where the existence of research process involving three parties as source of validation of information obtained. The subjects of this research are PKBM Geger Sunten, PKBM Kinanti, and PKBM Bina Terampil Mandiri which are all located in West Bandung Regency. The results of this study after the counseling through PKBM related to the utilization of ecological potential in cultural context, the surrounding community increasingly aware of the importance of ecological potential. It is seen that the community understanding around PKBM area has increased, ie PKBM Geger sunten from 33% to 75%, PKBM Kinanti from 37% to 72%, PKBM Bina skilled self-reliant from 25% to 70% and creativity began to emerge in the community in developing the potential to serve improve the economic capacity of the community